2000
DOI: 10.1136/ard.59.5.359
|View full text |Cite
|
Sign up to set email alerts
|

Systemic scleroderma in Greece: low mortality and strong linkage with HLA-DRB1*1104 allele

Abstract: Objective-Description of Greek patients with scleroderma with reference to (a) major organ disease, (b) autoantibodies, (c) survival rate, and (d) HLA associations. Methods-The clinical files of 254 patients were analysed retrospectively and a standardised clinical chart was completed with age at disease onset, sex, date of first and last visit, clinical and serological findings, organs aVected, reasons for death, and HLA class II alleles. HLA class II alleles (DRB1, DQA1, DQB1, DPB1) were determined by polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
2
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 47 publications
3
37
2
6
Order By: Relevance
“…39 of 54 (72%) patients who tested positive for ATA carried these alleles versus ,18% carriership in controls (p50.00006) [84]. Within HLA-DRB1*11, the allelic subtype *1104 seems to be associated with ATA positivity and the presence of lung fibrosis [85]. GILCHRIST et al [84] also showed that HLA DPB1*1301 was tightly associated with ATA presence.…”
Section: Pulmonary Fibrosis In Systemic Sclerosismentioning
confidence: 91%
See 1 more Smart Citation
“…39 of 54 (72%) patients who tested positive for ATA carried these alleles versus ,18% carriership in controls (p50.00006) [84]. Within HLA-DRB1*11, the allelic subtype *1104 seems to be associated with ATA positivity and the presence of lung fibrosis [85]. GILCHRIST et al [84] also showed that HLA DPB1*1301 was tightly associated with ATA presence.…”
Section: Pulmonary Fibrosis In Systemic Sclerosismentioning
confidence: 91%
“…Major histocompatibility complex Strong associations have been found between HLA-DRB1*11, and also HLA-DPB1*1301, and diffuse systemic sclerosis, and there is some evidence to suggest that it is an amino-acid motif, shared by the different class II susceptibility alleles, that may be pivotal in predisposing to autoantibody formation [84,85].…”
Section: Pulmonary Fibrosis In Systemic Sclerosismentioning
confidence: 99%
“…It is worth mentioning that none of the patients with RP expressed HLA-DRB1*04 and -DQB1*0302 alleles, which are also in linkage disequilibrium in the Greek population [27]. The above-mentioned negative association may define a protective haplotype against RP, a condition already noticed in several autoimmune diseases [27,28]. …”
Section: Discussionmentioning
confidence: 99%
“…5 Systemic sclerosis is found to be strongly associated with HLA-DRB1*1104 allele in the Greek community. 6 …”
mentioning
confidence: 97%